Legal Aspects Around Satellite Constellations - Froehlich, Annette; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book is based on an initiative made by the European Space Policy Institute, the European Centre for Space Law and the German Aerospace Center. Students and young professionals worlwide were invited to submit a paper on this topic analyzing and discussing relevant aspects on either environment, economy, security, licencing, or control. The best papers have been included in this volume.
An equitable and efficient use of outer space and its resources and the role of the UN, the ITU and States Parties -- The Principle of Equitable Access in the Age of Mega-Constellations.-- Legal Aspects Relating to Satellite Constellations -- The Rise of the LEO: Is there a need to create a distinct legal regime for constellations of satellites?- The Future impact of the ITU regulatory framework on Large Constellations of Satellites -- The Sustainability of Large Satellite Constellations: Challenges for Space Law -- Answering an orbit full questions: A proposed framework to provide legal certainty on the current and future state of the law regulating satellite constellations.
Keywords: Law of the sea; International law; Aeronautics -- Law and legislation; Solar system; Political science; Law of the Sea, Air and Outer Space; Space Physics; Political Science